Personal responsibility with health in Cuba: structural analysis and identification of strategic variables - Isabel Pilar Luis Gonzalvez; Adolfo Álvarez Pérez; Yusdanys Torres Jiménez (Medisur)
Background: the increase in personal responsibility for health in the Cuban population is an expected result of the Socialist Development Plan until the year 2030. To achieve this goal, a strategic planning exercise is needed. The structural analysis of the problem is the first stage of this exercise. Objective: to identify the variables related to the current and future levels of personal responsibility for health in the Cuban population, to describe the relationships between them and to determine those that, due to their levels of dependency and influence in the system, are strategic for promoting change. Methods: a strategic prospective study was carried out for the structural analysis of the levels of personal responsibility for health in Cuba. Through non-probabilistic sampling of critical cases, 24 experts were contacted who drew up a list of related variables to the study problem, assigned them and described the relationships between them. The cross-impact matrix-multiplication program applied to a classification was used for data analysis. Results: 19 variables were identified, of which five are determining variables, six challenge variables, two target variables and three result and autonomous variables, respectively. Intersectoral action, social norms and legal framework, paternalistic approach to health, individual and State-Government accountability, health literacy and support for care and well-being were considered strategic. Conclusions: the increase in the levels of personal responsibility for health will depend on intersectoral action, the updating of the legal framework and innovative forms for the accountability of all social actors. It will also be necessary to achieve improvements in health literacy, greater accompaniment to the efforts of individuals for self-care and the abandonment of paternalistic practices that expropriate citizens from their responsibilities.